2020
DOI: 10.3390/jrfm13050085
|View full text |Cite
|
Sign up to set email alerts
|

Current Research Trends on Interrelationships of Eco-Innovation and Internationalisation: A Bibliometric Analysis

Abstract: In this paper, bibliometric analysis is conducted on eco-innovation and internationalisation, since in the scientific literature, both research fields have been considered as being interrelated. Although the adoption of eco-innovation and internationalisation are risky processes, they reduce competitive risk and increase performance in a highly competitive business environment. The main objective of this study is to identify current research trends on the interrelationships of eco-innovations and international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…The query was validated by performing a review of each paper title and abstract to ensure that the final sample contains only papers with keywords that support the study objectives, as suggested by Sweileh [40], to ensure that the concise nature of keywords in the subject field are included. The documents were finally exported in a "txt" format immediately to prevent misinterpretation [40] and for further analysis [42].…”
Section: Search Strategymentioning
confidence: 99%
“…The query was validated by performing a review of each paper title and abstract to ensure that the final sample contains only papers with keywords that support the study objectives, as suggested by Sweileh [40], to ensure that the concise nature of keywords in the subject field are included. The documents were finally exported in a "txt" format immediately to prevent misinterpretation [40] and for further analysis [42].…”
Section: Search Strategymentioning
confidence: 99%
“…Previous investigators from a range of fields have used equivalent methodologies to those used in this article for the successful execution of comprehensive bibliometric analyses [19], [17], [18], [20], [21].…”
Section: Figure 1: the Five Stages Of A Bibliometric Analysismentioning
confidence: 99%
“…In the visualisation in Figure 6, the size of each circle represents the number of times an author has been cited. The circles' distances represent the relatedness, similarity, and cooperation between authors, while the different colours represent different clusters [30], [21].…”
Section: Co-citation Analysis Of Authorsmentioning
confidence: 99%
“…Notably, some studies, which investigated competitive advantage in relation to eco-innovation, did not distinguish the energy dimension. Furthermore, it is necessary to investigate competitive advantage in the context of international markets [84]. The explanation resides in the fact that a number of SMEs and especially from small and open economies, are forced to compete in the international arena.…”
Section: Micro-level: Agenda For Future Researchmentioning
confidence: 99%